Quantum Computing in 6G Networks: Revolutionizing Secure, Intelligent, and Optimized Communication for Future Digital Ecosystems - Kumar Sharma, Rajesh (Digital Repository of Theses, 2024)
Emerging technologies like quantum computing have the power to completely transform a number of computer and communication system components. Quantum computing is predicted to have a major impact on improving the capabilities of future networks as we approach the development of 6G. An overview of the incorporation of quantum computing in 6G systems is given in this abstract. Quantum computing processes data in ways that are fundamentally distinct from those of classical computing and are based on concepts from quantum mechanics. It makes use of quantum bits, or qubits, which can be in multiple states at once and make it easier to run complex computations in parallel. Quantum computing presents a number of opportunities as well as difficulties in relation to 6G. Secure communication and cryptography are two important areas of application. Many of the current encryption algorithms are vulnerable to quantum computing, hence creating quantum-resistant cryptographic techniques is essential for secure communication on 6G networks. Protocols for quantum key distribution (QKD), which allow cryptographic keys to be exchanged securely, Optimisation and resource management are two other areas where quantum computing can have a big influence. Large volumes of data will be handled by 6G networks, necessitating the effective use of network resources. Tasks like spectrum allocation, traffic management, and network routing can all be optimised with the use of quantum algorithms, improving energy efficiency and network performance.Moreover, advances in AI and machine learning may be made possible by quantum computing. Large datasets may be processed and analysed more quickly using quantum machine learning algorithms, which could enhance 6G systems' predictive models and decision-making abilities. However, incorporating quantum computing into 6G networks presents a number of difficulties. Since quantum computing is still in its infancy, there are still many obstacles to overcome before they can be used widely or scaled up. Furthermore, steady surroundings and extremely low temperatures are necessary for quantum computing, which makes it difficult to implement quantum systems in practical settings. To summarise, quantum processing can possibly fundamentally work on 6G organisations, particularly in the space of AI, cryptography, and advancement. In the 6G era, further research and development in quantum technologies will pave the way for their integration into upcoming communication systems, opening up new possibilities and capacities despite the existence of obstacles. The purpose of research is to explore the Quantum paradigm revolution across the different businesses . The Data communication will be fully secured for Device to Device (D2D ) and Device to Cloud (D2C) communication with Quantum safe cryptography . It will enhance the communication security for Industry 4.0 and 5.0 . Next generation generation Metaverse systems need utmost security , beside AI immersive technologies such as AR/VR/MR/XR, 6G and edge computing are essentials for producing versatile and resilient meta verse . With 6G communication capabilities, communication across land , water and space is possible. Highly reliable and ultra-fast satellite powered internet will thrive in the 6G with mandate of Data Security across the network .When 6G era commences real world quantum computing will start flourishing . Thus quantum safe security solutions have to be in place to ensure versatile and resilient communication.